Functions, Scope and Advantages of Management accounting : A Review - NAMITA (Innovative Research Thoughts, 2017)
Accounting is the process of recording, classifying, summarizing, analyzing and interpreting the financial transactions of the business for the benefit of management and those parties who are interested in business such as shareholders, creditors, bankers, customers, employees and government. Thus, it is concerned with financial reporting and decision making aspects of the business.